Desenvolvimento de um método para projetar, analisar e controlar o processo de fabricação em tempo real de um produto farmacêutico empregando ferramentas quimiométricas e infravermelho - Kondo, Simone Mayumi (2023)
Innovation and continuous improvements in manufacturing processes to produce high quality drugs in a short period of time has been a great challenge in the pharmaceutical industries. The use of Process Analytical Technology (PAT) will be a mechanism for designing, analyzing, and controlling pharmaceutical manufacturing processes by determining critical process parameters that affect quality attributes. This whole process takes place online or with the use of tools that allow greater speed. Thus, the objective of this professional master's project is to develop a method that will be used to control the manufacturing process of a drug using tools for acquisition and analysis of multivariate data. The target of the project will be a pharmaceutically solid oral drug containing pellets with an active in a capsule. The pellets of this product have layers of active and coating. In the development of this project were evaluated data related to the layers that line the pellets, which was identified as a critical stage of the process. Data from the development phase and the product approved for commercialization were evaluated in order to control the process and make adjustments, when necessary, based on data analysis, and detect errors or deviations, and correct them during their manufacture. The data was obtained with the Near-infrared spectroscopy (NIR) method, an analysis tool that allows great agility during the process.